2020
DOI: 10.1590/0037-8682-0509-2019
|View full text |Cite
|
Sign up to set email alerts
|

Case series of sporotrichosis at a teaching hospital in Brazil

Abstract: Introduction: Sporotrichosis is a subcutaneous fungal infection with a worldwide distribution and higher incidence in tropical and subtropical areas, such as the Brazilian territory, where it has been standing out due to its frequent epidemics. Thus, the present study aimed to evaluate the prevalence of sporotrichosis and profile the affected patients at a university teaching hospital in the central region of Rio Grande do Sul, Brazil. Methods: This study was a case series of patients diagnosed with Sporothrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 20 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…After analyzing the articles to carry out the classification according to the new taxonomy, we found that the most common reported etiological agent was Sporothrix spp. with 94.34% (11,922/12,636), followed by S. schenckii with 3.16% (400/12,636), S. brasiliensis with 1.21% (153/12,636), S. globosa plus S. schenckii with 0.72% (91/12,636), S. globosa with 0.51% (65/12,636), S. mexicana 0.03% (4/12,636), and S. pallida with 0.007% (1/12,636) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ,…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…After analyzing the articles to carry out the classification according to the new taxonomy, we found that the most common reported etiological agent was Sporothrix spp. with 94.34% (11,922/12,636), followed by S. schenckii with 3.16% (400/12,636), S. brasiliensis with 1.21% (153/12,636), S. globosa plus S. schenckii with 0.72% (91/12,636), S. globosa with 0.51% (65/12,636), S. mexicana 0.03% (4/12,636), and S. pallida with 0.007% (1/12,636) [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 ,…”
Section: Discussionmentioning
confidence: 99%
“…A total of 68 publications with 11,050 cases of sporotrichosis were found in South America [ 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 , 101 , 102 , 103 , 104 , 105 , 106 , 107 , 108 , 109 , 110 , 111 , 112 , 113 , 114 , 115 , 116 , 117 , 118 , 119 , 120 …”
Section: Epidemiology Of Sporotrichosis In South Americamentioning
confidence: 99%
See 3 more Smart Citations